Smart vertical garden system design and performance for indoor vegetable production - Hamidon, Munirah Hayati (2019)
Vertical garden systems have the potential to increase vegetables production in the urban areas in Malaysia. The purposes of this research were to design and develop a compact and smart vertical garden system for urban agriculture and to study the growth of lettuces in the developed vertical system. The development of the smart vertical garden system was divided into two main components: i) the development of vertical garden system and ii) the monitoring system for nutrients solutions. The main parts of the structure comprised of water tank, extendable pole as the support, irrigation line and five stacks of planting pots with each pot had eight planting pockets. The gravity-fed irrigation method was used to irrigate all the lettuces in the vertical garden. The water quality monitoring system consisted of EC and pH sensors that integrated with Arduino Uno microcontroller. The growth of lettuce (Lactuca sativa) was observed at the different stacks of the vertical garden system. Besides, the plant growth development in the designed vertical garden was compared with a commercialized conventional hydroponic system. As for the plant growth development in the vertical garden between stacks, the result showed that the maximum lettuces height, leaves width and number of leaves were found at the most bottom stack (stack 5). From the overall ANOVA results, only lettuce height was observed to be significantly difference (P < 0.0001) at the different stacks while no significant difference was observed in the overall number of leaves produced (P = 0.0002) and leaves width (P = 0.0046) at the different level of stacks. The growth development of the lettuces at each of the stacks was varied due to different amount of water and light exposure. While comparing the development of plants grown in vertical garden and commercialized conventional hydroponic system, there was no significant difference in each of the lettuces growth parameters (lettuce height (P = 0.4997); number of leaves (P = 0.5325); and width leaves (P= 0.5231)). To conclude, the designed vertical garden performed similarly as the commercial conventional hydroponic system. Hence, the vertical garden has a great potential to be as one of the planting alternative system especially in limited space area.